ANALISIS PERBANDINGAN GOOD CORPORATE GOVERNANCE BAZNAS DAN LAZNAS - Sri Wahjuni Latifah; Siska Aprilia; Dhaniel Syam (UNIB Press, 2019)
Abstrak Penelitian ini bertujuan untuk menganalisis perbandingan Good Corporate Governance ( Badan Amil Zakat nasional) dan Laznas(Lembaga Amil Zakat Nasiona. Sampel penelitian ini sebanyak delapan belas(18) Baznas dan Laznas di Jawa Timur. Jenis dan sumber data diperoleh dari laporan tahunan badan atau lembaga amil zakat nasional di Jawa Timur tahun 2016-2017 yang diterbitkan di website resmi pid.baznas.go.id. Data dianalisis dengan beberapa tahap, yaitu melakukan content analysis dan dilakukan uji hipotesis dengan Mann Whitney U Test. Hasil penelitian menunjukkan uji Mann Whitney U Test sebesar 0.003, dengan demikian terdapat perbedaan yang signifikan terhadap penerapan GCG Baznas dengan Laznas. Baznas lebih baik dalam menerapkan good corporate governance dibandingkan pada Laznas.Kata Kunci: Baznas, Laznas, Good Corporate Governance.AbstractThis study aims to compare the good corporate governance of the Baznas(Amil Zakat Agency) and Laznas(the National Amil Zakat Institution). The samples used in this study were 18 Amil Zakat Bodies and Amil Zakat Institutions. The types and sources of data are obtained from the annual report of the national amil zakat agency or institution in East Java for 2016-2017 which is published on the official website of pid.baznas.go.id. The analysis technique in this study was to conduct content analysis, then carried out hypothesis testing with the Mann Whitney U Test. The Mann Whitney U Test results of 0.003 , which means there are significant differences. Based on the results of the study, the authors can conclude that there are differences in the application of good corporate governance at the Baznas with Laznas. The Baznas is better at implementing good corporate governance than at the Laznas.Keywords: Baznas, Laznas, Good Corporate Governance.